Inflation heterogeneity at the household level - Georg Strasser; Teresa Messner; Fabio Rumler; Miguel Ampudia (European Central Bank (ECB), 2023)
Inflation affects the purchasing power of households. This paper documents large, idiosyncratic inflation differences between households in their everyday shopping. Low-income households have experienced higher inflation in the last ten years, but the difference for richer households has been small and time varying. Householdspecific behaviour appears to dominate inflation differences within countries. Between countries, multinational retail chains not only differentiate products by branding, but also charge different prices for identical products. Retailers continue to differentiate prices along national borders, even within largely integrated economic regions. Price changes, however, are broadly aligned across borders within the same retailers.
Keywords: D12; D3; D43; E31; F15; F4; 330; inflation; consumer prices; heterogeneous agents; substitution; inequality